EFFECTS OF MORINGA OLEIFERA, A PLANT EXTRACT CODED OBAYOKOU ON ULCERS CAUSED BY MYCOBACTERIUM ULCERANS IN CHILDREN UNDER 15 YEARS IN CÔTE D'IVOIRE (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
The aqueous extract of a plant coded OBAYOKOU (Moringa oleifera ) has been tested on the healing of ulcers in children under 15 years, two lots of 15 children each were made all presenting clinical forms of Buruli ulcer. The aqueous plant extract of Moringa oleifera was added to the food supply given to Lot B (lot of experimental subjects) at a rate of 330 ml per meal per child for six weeks. Children of Lot A (control Lot) received normal diet without Moringa oleifera. The results of this study have shown that children in (lot B) in addition to the normal diet received 330 ml of Moringa oleifera per meal, had a higher rate of healing than Lot A (Witness Lot) who received only normal diet. Thus, the rate of healing of ulcers with M. oleifera (24 mm) is superior to healing without M. oleifera (10 mm) after six weeks. This study shows that we can overcome Buruli ulcer with medicinal plants that is abundantly available in Africa. It also shows that it is necessary to conduct research on a wider range of fractions of Moringa oleifera to improve the activity of antimycobacteriennes molecules in the aqueous extract of Moringa oleifera.